2015
DOI: 10.1186/s12872-015-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ischemic infarction and stenosis of intra- and extracranial arteries in young Chinese patients with ischemic stroke

Abstract: BackgroundThe distribution of cerebral ischemic infarction and stenosis in ischemic stroke may vary with age-group, race and gender. This study was conducted to understand the risk factors and characteristics of cerebral infarction and stenosis of vessels in young Chinese patients with ischemic stroke.MethodsThis was a retrospective study, from January 2007 to July 2012, of 123 patients ≤50 years diagnosed with acute ischemic stroke. Patient characteristics were compared according to sex (98 males and 25 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
(58 reference statements)
4
7
0
Order By: Relevance
“…In a German nationwide case-control study involving 2125 young stroke patients, eight cardiovascular risk factors combined could explain 78.9% of all strokes [16]. In our study, we found that 83.5% patients has two or more traditional vascular risk factors and the most frequent traditional vascular risk factors include hypertension, hyperlipemia, smoking and alcohol consumption, which is consistent with previous studies [4,17]. We also found that hyperhomocysteinemia, an independent risk factor of stroke, is prevalent in young stroke patients, which has rarely been reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a German nationwide case-control study involving 2125 young stroke patients, eight cardiovascular risk factors combined could explain 78.9% of all strokes [16]. In our study, we found that 83.5% patients has two or more traditional vascular risk factors and the most frequent traditional vascular risk factors include hypertension, hyperlipemia, smoking and alcohol consumption, which is consistent with previous studies [4,17]. We also found that hyperhomocysteinemia, an independent risk factor of stroke, is prevalent in young stroke patients, which has rarely been reported.…”
Section: Discussionsupporting
confidence: 92%
“…However, these data was mainly collected from European populations. In a study involving 123 Chinese young adults, LAA and small vessel disease (SVD) were the most common causes of acute ischemic stroke [4]. Other studies also showed that proportion of LAA was higher in Asians than that in western populations, indicating that cerebral artery stenosis may be an important cause of stroke in Asian populations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…All patients were up to 18 years old and received throat swab samples which were gathered for SARS-CoV-2 RNA detection by gene sequencing or real-time RT-PCR and the results were positive at least once. Diabetes mellitus was defined as a medical history of diabetes or the use of oral hypoglycemic medication or insulin or patients with a fasting glucose ≥7.0 mmol/L or a two-hour postprandial serum glucose ≥11.1 mmol/L [7]. Hypertension was defined as a medical history of hypertension or the use of antihypertensive, a systolic blood pressure of ≥140 mmHg and/or a diastolic blood pressure of ≥90 mmHg [8].…”
Section: Definitionsmentioning
confidence: 99%
“…Moreover, ICAS was most common in young Chinese patients with ischemic stroke, likely due to high exposure to hypertension, smoking, dyslipidemia, and diabetes. 23 , 24 Thus, more attention and further studies are required for these special subgroups.…”
Section: Epidemiologymentioning
confidence: 99%
“…Many studies indicate that vascular risk factors, including hypertension, diabetes mellitus, hyperlipidemia, family history of stroke and heart disorders, smoking, heavy drinking, hyperhomocysteinemia, and overweight, are associated with ICAS. 2 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 However, there are some inconsistencies in the data. Unlike the CICAS study, most studies are limited by, for example, small sample sizes and single-center, retrospective designs.…”
Section: Etiologymentioning
confidence: 99%